2008
DOI: 10.1002/anie.200703082
|View full text |Cite
|
Sign up to set email alerts
|

Facile Incorporation of Platinum(IV) into Polyoxometalate Frameworks: Preparation of [H2PtIVV9O28]5− and Characterization by 195Pt NMR Spectroscopy

Abstract: A new mate for vanadate: The platinum(IV)‐containing polyoxovanadate [H2PtIVV9O28]5− (1) has been synthesized and structurally characterized (see polyhedral representation). The characterization of polyanion 1 in solution by 195Pt NMR spectroscopy is unprecedented in POM chemistry. The facile synthetic procedure with the PtIV precursor H2Pt(OH)6 appears to be a convenient and general methodology for making a large variety of PtIV‐containing polyoxometalates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 93 publications
(86 citation statements)
references
References 24 publications
9
77
0
Order By: Relevance
“…[2,3,5] [a] School of Engineering 5-). In the case of dilacunary polyoxotungstates our calculations confirm the necessity of modelling an ion pair in which a counterion is specifically included in the POM lacuna to attain accurate predictions of the corresponding 183 W NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,5] [a] School of Engineering 5-). In the case of dilacunary polyoxotungstates our calculations confirm the necessity of modelling an ion pair in which a counterion is specifically included in the POM lacuna to attain accurate predictions of the corresponding 183 W NMR spectra.…”
Section: Introductionmentioning
confidence: 99%
“…2.5) of one of several other platinum-substituted decavanadate species peripherally reported by us, [1] Hill et al have overlooked the fact that the formulation reported here or indeed in any crystal structure is an average over the entire crystal. Stochastic disorder and/or presence of hydrogen atoms (or other atoms) on or close to special positions will inevitably lead to fractional occupancies.…”
mentioning
confidence: 84%
“…They draw attention to some perceived problems with our recent paper in this journal [1] reporting the isolation and structural characterization of [H 2 Pt IV V 9 O 28 ] 5À (1); they argue that an anion, a-[SiW 10 Pt…”
mentioning
confidence: 96%
“…[5,[12][13][14] Furthermore, terminal metal oxo species exhibit the only multiple noble-metal-oxygen bonds and such species should not exist based on electronic structure arguments. [5,13,14] [11] (cited as reference [12] in reference [1]) the (guanidinium) 8 ({SiW 11 }). First, the infrared spectra of the crystalline guanidinium salts of {SiPt 2 W 10 } prepared using the exact published procedure of Lee et al, [11] and {SiW 11 } are identical (Figure 1 a).…”
Section: àmentioning
confidence: 99%